Indoctrination Against Women in "The Lowland" by Jhumpa Lahiri - Arianto, Tomi; Ambalegin, Ambalegin (OKARA: Jurnal Bahasa dan Sastra, 2018)
Indoctrination is one form to limit women's space unnoticed. Through indoctrination, a woman will not feel that her space of motion has been restricted. It is because the indoctrination done based on conventions, as well as traditions that exist in the community. This is reflected in the Lowland novel written by Jhumpa Lahiri. The Lowland novel provides an overview the position of women in India who are 'voluntarily' restricted by the indoctrination. Indoctrination reflected in customs, traditions and other things. It is represented by the character Gauri that almost all aspects of her life are determined by men. This research is done by applying the concept of the scope of women carried by Barbara Welter. This is a concept that women's movement space tends to be limited by the existence of constructions. The results indicated that Indoctrination contestation in the novel The Lowland is divided into four forms; piety, purity, submissiveness and domesticity. Lowland's novel is also a representation of feminism. Customary and community traditions are points criticized by Lahiri. What experienced by Gauri as a woman in the patriarchal society convention was also experienced by many women in India. The space for movement becomes limited due to indoctrination with the labels of religion, norms, customs and traditions.